2012
DOI: 10.2298/ciceq120110112j
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of long-term exposure to air pollution: An overview of major respiratory and cardiovascular diseases and diabetes

Abstract: Large number of studies provided convincing evidence for adverse effects of exposure to outdoor air pollution on human health, and served as basis for current USA and EU Air Quality Standards and limit values. Still, new knowledge is emerging, expanding our understanding of vast effects of exposure to air pollution on human health of this ubiquitous exposure affecting millions of people in urban setting. This paper focuses on the studies of health effects of long-term (chronic) exposures to air pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The link between PM 10 and adverse health effects was first established in the 1990s, where epidemiological studies found a positive association between the level of particulate air pollution in cities and increased morbidity and mortality rates in both adults and children, with adverse health effects being manifested predominantly in susceptible individuals who had pre-existing pulmonary or cardiovascular disease [ 12 , 13 ]. It is now widely accepted that exposure to PM 10 may cause or exacerbate allergic respiratory diseases (e.g., asthma) [ 14 ], chronic obstructive pulmonary disease, pneumonia, and cardiovascular disease [ 15 ] and is also defined as a definite carcinogen by International Agency for Research on Cancer (IARC) [ 16 ]. The cellular and molecular mechanisms underlying the toxicity of inhaled particles has been extensively investigated, and hypothesised to be driven by the stimulation of inflammation and/or oxidative stress [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The link between PM 10 and adverse health effects was first established in the 1990s, where epidemiological studies found a positive association between the level of particulate air pollution in cities and increased morbidity and mortality rates in both adults and children, with adverse health effects being manifested predominantly in susceptible individuals who had pre-existing pulmonary or cardiovascular disease [ 12 , 13 ]. It is now widely accepted that exposure to PM 10 may cause or exacerbate allergic respiratory diseases (e.g., asthma) [ 14 ], chronic obstructive pulmonary disease, pneumonia, and cardiovascular disease [ 15 ] and is also defined as a definite carcinogen by International Agency for Research on Cancer (IARC) [ 16 ]. The cellular and molecular mechanisms underlying the toxicity of inhaled particles has been extensively investigated, and hypothesised to be driven by the stimulation of inflammation and/or oxidative stress [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a number of health problems have been associated with high concentrations of PM [23]. Exposure to PM of indoor air has been linked to many different diseases, including acute and chronic respiratory diseases, tuberculosis, heart disease, asthma, lung cancer, cardiovascular disease and perinatal health outcomes.…”
mentioning
confidence: 99%
“…There are several studies that indicate links between air pollution, especially ambient air particulate matter (PM), and both short-term and long-term health effects [ 1 ]. It is now widely accepted that exposure to PM may cause or exacerbate allergic respiratory diseases (e.g., asthma), pneumonia, chronic obstructive pulmonary disease (COPD) and cardiovascular disease [ 2 ], and is classified as a human carcinogen by International Agency for Research on Cancer (IARC) [ 3 ]. The cellular and molecular mechanisms underlying the toxicity of inhaled particles has been extensively investigated, and hypothesised to be driven by the stimulation of inflammation and/or oxidative stress [ 4 ].…”
Section: Introductionmentioning
confidence: 99%